2018
DOI: 10.3892/etm.2018.6895
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‑200a functions as a tumor suppressor by targeting FOXA1 in glioma

Abstract: microRNAs (miRs) serve primary roles in certain human malignancies; however, the detailed regulatory mechanism of miR-200a in glioma progression is yet to be fully elucidated. The current study aimed to assess the expression of miR-200a in glioma as well as the regulatory mechanism of miR-200a in glioma cell proliferation, survival and invasion. RT-qPCR and western blotting were performed to examine mRNA and protein expression. An MTT assay, an EdU incorporation cell proliferation assay and a transwell assay w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…The miR-200 family (miR-200a, -200b, -200c, -141, and -429) has been demonstrated as an inhibitor of epithelial-tomesenchymal transition (EMT) and metastasis of cancer in colon (Hur et al, 2013). Chen et al (2019) reported that miR-200a is a tumor suppressor in glioma by directly targeting forkhead box A1 (FOXA1). FOXA1 is a transcription factor that is essential for epithelial lineage differentiation, playing an oncogenic or tumor-suppressive role in human malignancies (Song et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The miR-200 family (miR-200a, -200b, -200c, -141, and -429) has been demonstrated as an inhibitor of epithelial-tomesenchymal transition (EMT) and metastasis of cancer in colon (Hur et al, 2013). Chen et al (2019) reported that miR-200a is a tumor suppressor in glioma by directly targeting forkhead box A1 (FOXA1). FOXA1 is a transcription factor that is essential for epithelial lineage differentiation, playing an oncogenic or tumor-suppressive role in human malignancies (Song et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…miR-200a is an important member of the miR-200 family. It has been reported that miR-200a participates in several biological processes to control the progression of cancer [26,27]. miR-200a was shown to target FOXA1 and act as a tumour suppressor in the survival, proliferation and invasion of glioma cells [27].…”
mentioning
confidence: 99%
“…It has been reported that miR-200a participates in several biological processes to control the progression of cancer [26,27]. miR-200a was shown to target FOXA1 and act as a tumour suppressor in the survival, proliferation and invasion of glioma cells [27]. In addition, miR-200a might inactivate BRD4-mediated AR signalling to inhibit the progression of prostate cancer [26].…”
mentioning
confidence: 99%
“…MiR-200a was an important member of miR-200 family. It had been reported that miR-200a was involved in several biological processes to control progression of cancer [27,28]. MiR-200a was showed to target FOXA1 and acts as a tumor suppressor on the survival, proliferation and invasion of glioma cells [28].…”
Section: Dennd5b-as1 Dleu2 Grm7-as3 Linc00303 Linc00473 Meg3 Mymentioning
confidence: 99%
“…It had been reported that miR-200a was involved in several biological processes to control progression of cancer [27,28]. MiR-200a was showed to target FOXA1 and acts as a tumor suppressor on the survival, proliferation and invasion of glioma cells [28]. And miR-200a might inactivate BRD4-mediated AR signaling to inhibit progression of prostate cancer [27].…”
Section: Dennd5b-as1 Dleu2 Grm7-as3 Linc00303 Linc00473 Meg3 Mymentioning
confidence: 99%